Continuity in Partially Ordered Sets - Venu G. Menon (International Journal of Mathematics and Mathematical Sciences)
The notion of a continuous domain is generalized to include posets which are not dcpos and in which the set of elements way below an element is not necessarily directed. We show that several of the pleasing algebraic and topological properties of domains carry over to this setting.